Relationship of thyroid parameters with chronic inflammation in patients with euthyroid type 2 diabetes - Shi, Wei; Chen, Dan; Chen, Wei; Chen, Yulu; Fu, Xiaoling; Xiao, Yong; Duan, Wei; Zhang, Jing (Frontiers in Endocrinology, 2024)
Aims: We evaluated the association of multiple thyroid parameters with the levels interleukin 6 (IL6) and interleukin 8 (IL8) in patients with euthyroid type 2 diabetes (T2D). Methods: A total of 166 adults with euthyroid T2D were examined. Serum IL6, IL8, triiodothyronine (FT3), free thyroxin (FT4), thyroid-stimulating hormone (TSH), five thyroid sensitivity indexes (FT3/FT4, TSH index [TSHI], thyrotroph T4 resistance index [TT4RI], thyroid feedback quantile-based index by FT3 [TFQIFT3], and TFQIFT4), and biochemical parameters were determined. Results: The median age was 64 years (IQR: 54.75,70) and the median duration of diabetes was 10 years (IQR: 3,18). Patients with high levels of IL6 (≥2.38 pg/mL) had lower levels of FT3 and TFQIFT3 (P<0.05). Patients with high levels of IL8 (≥18.1 pg/mL) had lower levels of TSH and higher levels of FT4 (P<0.05). IL6 was negatively correlated with FT3 (r=−0.359, P<0.001), TFQIFT3 (r=−0.273, P=0.009), and FT3/FT4 (r=−0.22, P=0.037). IL8 was negatively correlated with TSH (r=−0.256, P=0.01), TSHI (r=−0.226, P=0.033), and TT4RI (r=−0.244, P=0.021). Binary logistic regression analysis with multiple adjusted models showed that a high level of IL6 was negatively associated with FT3 (aOR: 0.529; 95%CI: 0.302, 0.926, P=0.026), and that a high level of IL8 was negatively associated with TSH (aOR: 0.343; 95%CI: 0.155, 0.759; P=0.008) and TT4RI (aOR: 0.398;95%CI: 0.191, 0.831; P=0.014). Conclusion: Patients with euthyroid T2D who had lower levels of FT3 had significantly higher levels of IL6, and those with lower levels of TSH and TT4RI had significantly higher levels of IL8.